2005
DOI: 10.1243/135065005x9754
|View full text |Cite
|
Sign up to set email alerts
|

Film pressure distribution in water-lubricated rubber journal bearings

Abstract: Measurements of fluid film pressures were made on water-lubricated rubber journal bearings. The measurements indicated that the film pressure profiles are very different from those of conventional rigid bearings. The relatively low film pressures caused significant rubber deflections but were too low to produce lubricant viscosity changes. Integration of the pressure in the bearings showed that they operate in the regime of mixed lubrication. The behaviour of the bearings was theoretically investigated using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 3 publications
1
45
0
1
Order By: Relevance
“…However, due to the restriction of many factors (sealing of film space, formation mechanism of film, and various bearing structures), the multi-points monitoring must be conducted, and the measurement for film pressure of bearings is hard to be achieved [11]. At present, there are two on-line monitoring methods, one method is that the pressure sensors are installed in the measuring holes punched on the shaft, and the data of film pressure is transmitted using the brush or mercury collection rings [12]. But the contact of ring produces more noises, which greatly affect the pressure, and furthermore, the reliability and the high cost of ring make its application limited.…”
Section: Wireless Testing Methods Of Water-lubricated Bearingmentioning
confidence: 99%
“…However, due to the restriction of many factors (sealing of film space, formation mechanism of film, and various bearing structures), the multi-points monitoring must be conducted, and the measurement for film pressure of bearings is hard to be achieved [11]. At present, there are two on-line monitoring methods, one method is that the pressure sensors are installed in the measuring holes punched on the shaft, and the data of film pressure is transmitted using the brush or mercury collection rings [12]. But the contact of ring produces more noises, which greatly affect the pressure, and furthermore, the reliability and the high cost of ring make its application limited.…”
Section: Wireless Testing Methods Of Water-lubricated Bearingmentioning
confidence: 99%
“…Pai et al [2] studied the non-linear analysis of water-lubricated journal bearings having multiple axial grooves under unidirectional constant load, unidirectional periodic load, and variable rotating load. Cabrera et al [3] and Geng et al [4] measured the lubricant film pressure of water-lubricated rubber journal bearings. Dai et al [5] presented a new water lubrication hybrid journal bearing that had round recess and cooling orifice restrictors for limiting temperature rise on the surface of bush directly and had stepped recesses for enhancing dynamic effect.…”
Section: Structure Of High Speed Sleeve Bearing With Low Viscositmentioning
confidence: 99%
“…Cabrera et al [28] studied the film pressure distribution in water lubricated rubber journal bearings. The measurements of pressure indicated that the film pressure profiles are very different from those of the conventional rigid bearings.…”
Section: Review Of Literaturementioning
confidence: 99%